Beyond interferon gamma - decreased cellular response to COVID-19 vaccination booster in patients with autoimmune inflammatory rheumatic diseases - Wroński, Jakub; Massalska, Magdalena; Jaszczyk, Bożena; Felis-Giemza, Anna; Kornatka, Anna; Plebańczyk, Magdalena; Burakowski, Tomasz; Kwiatkowska, Brygida; Kuca-Warnawin, Ewa; Ciechomska, Marzena (Frontiers in Immunology, 2025)
The global COVID-19 pandemic has led to significant advancements in vaccine research, particularly regarding patients with autoimmune inflammatory rheumatic diseases (AIIRD). However, most studies have assessed the post-vaccination cellular response only by measuring the production of interferon-gamma. This study aimed to explore the post-vaccination cellular immune response in patients with AIIRD, with a focus on the effects of immunomodulatory drugs on different proteins involved in the cellular response and cytotoxicity. We analyzed blood samples from 54 patients - 16 healthy controls (HC) and 38 AIIRD patients - at three time points: before (T0), 4 weeks after (T1), and more than 6 months after (T2) a COVID-19 booster vaccination. Gene expression and concentration levels of 13 proteins involved in cellular immunity were assessed. Our study showed significantly reduced production of TNF at T0, IL-2 at T0 and T2, and perforin at T2 in AIIRD patients compared to HC. In AIIRD patients the expression of genes involved in cytotoxicity, including NRF2, TRAIL, cathepsin B, and cathepsin H was impaired. Both protein concentrations and gene expression were particularly altered in those treated with glucocorticoids, methotrexate, and biologic/targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs). Among b/tsDMARDs only IL-17 inhibitors did not affect the cellular response. These findings suggest that COVID-19 vaccination elicits a weakened cellular response in patients with AIIRD, particularly those on immunosuppressive therapies, potentially compromising vaccine efficacy. Further studies are required to determine the clinical impact of these findings on long-term vaccine effectiveness in this population.